2022
DOI: 10.1155/2022/2361507
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Immune Microenvironmental Landscape of Lung Squamous Cell Carcinoma with Immune Cell Infiltration

Abstract: Background. Increasing evidence supports that immune cell infiltration (ICI) patterns play a key role in the tumor progression of lung squamous cell carcinoma (LUSC). However, to date, the immune infiltration picture of LUSC has not been elucidated. Method. TCGA was used to download multiomics data from LUSC samples. At the same time, we included two datasets on lung squamous cell carcinoma, GSE17710 and GSE157010. To reveal the landscape of tumor immune microenvironment (TIME), the ESTIMATE algorithm, ssGSEA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…This observation may potentially contribute to the unfavorable prognosis associated with these subtypes. Cohorts of patients undergoing immunotherapy have confirmed that those with higher ICI scores exhibit notable therapeutic benefits and clinical advantages [127]. The findings of this study provide evidence supporting the utility of ICI scores as a reliable prognostic biomarker and predictive indicator for immunotherapy.…”
Section: The Prognostic Value Of Tmb and The Relationship Between Tmb...supporting
confidence: 69%
“…This observation may potentially contribute to the unfavorable prognosis associated with these subtypes. Cohorts of patients undergoing immunotherapy have confirmed that those with higher ICI scores exhibit notable therapeutic benefits and clinical advantages [127]. The findings of this study provide evidence supporting the utility of ICI scores as a reliable prognostic biomarker and predictive indicator for immunotherapy.…”
Section: The Prognostic Value Of Tmb and The Relationship Between Tmb...supporting
confidence: 69%
“…Lung cancer is one of the deadliest malignancies in the world and is the primary cause of death among cancer patients ( Siegel, Miller & Jemal, 2020 ; Mridha et al., 2022 ; Adams et al., 2023 ). Lung squamous cell carcinoma (LUSC) belongs to non-small-cell lung cancer (NSCLC), and clinical statistics show that the number of patients with LUSC accounts for about 30% of patients with NSCLC ( Li et al., 2022a ; Ding et al., 2022 ; Chen et al., 2022a ; Pan et al., 2022 ). In recent years, conventional platinum-based two-drug therapy and combination chemotherapy have remained the first-line treatments for advanced LUSC.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they observed favorable clinical outcomes correlated with TTN mutations. Furthermore, within the 389 gene signature panel, we identified genes such as (i) ACE2, recognized for its involvement in innate immunity; (ii) TRIM51, which exhibits increased expression in patients with high immune cell infiltration (Chen et al, 2022); (iii) SERPINB4, whose high mutation frequency correlates with improved survival postimmunotherapy in melanoma patients (Riaz et al, 2016); and (iv) ADAM2, whose expression enhances the cytotoxicity of CD8 T-cells (Dervovic et al, 2023). These findings underscore the potential of our panel not only for TMB assessment but also for uncovering crucial immunoregulatory mechanisms underlying tumor response to therapy.…”
Section: Discussionmentioning
confidence: 99%